Influence of Soil Parent Materials and Soil-Related Factors on the Growth and Yield of Rubber Under Felcra Scheme, Sendayan - Auxtero, Edgardo Antiga (1986)
The influence of two terrain classes (i.e. 5 to 25% and 25 to 50% slopes) on soils developed from two parent materials (i.e. granite and sedimentary rocks) on the growth and yield of rubber (Hevea brasiliensis) after four years of tapping was evaluated by using the field data, viz. girth and yield of rubber from 1980 to 1983, obtained from the Federal Land consolidation and Rehabilitation Authority (FELCRA) Scheme at Sendayan, Negri Sembilan. RUbber grown on sedimentary rock derived soil on steep slopes (25 to 50% slope) after four years of tapping showed significantly bigger girth than those grown on same soil on undulating to rolling terrain (5 to 25% slope). The mean monthly and yearly dry weight of rubber after four years of tapping was significantly higher in areas planted on sedimentary rock derived soils located on steep terrain. The growth of rubber as influenced by the interaction of parent material and slope over time was not significant during the same period of tapping. However3 the overall yield of rubber was significantly higher on soils derived from sedimentary rocks on steep terrain than on soils derived from granite on similar terrain.